“Masnaviyi Manaviy” and Uzbek Literature - Rahimboevich , Tukhsanov Kahramon (Miasto Przyszłości, 2025)
The article discusses the role of the “Masnavi” in Uzbek literature. It is said that one of the pearls of importance in two aspects among these works is the “Masnavi” of the great sheikh, the scholar of the science of Sufism Maulana Jalaliddin Rumi, in which the essence and content of the Qur’an and sacred hadiths are in harmony with Sufi views.